(untitled) (Journal of Astronomy & Earth Sciences Education, 2017)
Considerable debate exists among discipline-based astronomy education researchers about how students change their perceptions in science and astronomy. The study questioned the development of astronomical models among students in institutions of higher education by examining how college students change their initial conceptual frameworks and construct mental models in astronomy. The study considers four areas of astronomical knowledge: "sky observations," "Earth and its orbit," "solar system" and "stars” by implementing a recently developed research tool - Conceptual Frameworks in Astronomy (CFA) (Pundak, 2016). The responses of 537 undergraduates from three Israeli colleges were classified into one of four mental models: pre-scientific, geocentric, heliocentric, stellar/scientific. The findings indicate significant differences among students adopting some combination of the four mental models. Most students adopted a combination of these models and used different conceptual frameworks for different astronomical phenomena. Students with a scientific engineering background tended to use the stellar/scientific model more often than Liberal Arts students. The stellar/scientific model is the most scientifically progressive of the four models tested and manages the most systematic astronomical conceptual frameworks. The study identified three variables: "physical background," "average academic grade" and "academic discipline" - which contribute to the adoption of the stellar/scientific model.